Nutritional labeling of prepackaged food products in the purchasing decision: The case of Peru and Mexico - Caramutti-De La Piedra, Rosalía (2024)
Nutritional labeling of food products educates and generates consumer learning about healthy ingredients, quality and nutritional value. We analyze the perception of the elements of the labeling of prepackaged foods and non-alcoholic beverages that could be considered in the consumer’s purchasing decision. The characteristics that the consumer identifies as critical nutrients that would represent a risk to their health if excessive consumption are made known. Using qualitative (interview) and quantitative (survey) methodology, with non-probabilistic sampling, which included women and men from Peru and Mexico, between 18 and 60 years old, consumers of prepackaged foods and non-alcoholic beverages; It is concluded that Peru and Mexico have favorable learning of healthy practices and use of regulations; they must provide nutritional education to consumers to choose foods in order to achieve a healthier diet. Although there is awareness of risks, they are consumed by practicality and easy access.